Role of mobile technology in the construction industry – a case study. (28th January 2009) - Venkatraman, Sitalakshmi; Yoong, Pak
The construction industry is facing a number of pressures to decrease costs, improve productivity and have a competitive edge in terms of quality of service and customer satisfaction. Recent advancements in mobile technology provide new avenues for addressing this situation. This paper presents the role of emerging mobile technologies and, in particular, the development of a mobile facsimile solution that assists collaborative communications between parties on or away from the construction site. This paper first identifies potential use cases for mobile technologies in the construction industry and highlights the issues that would hamper their adoption. It discusses the modelling of the problems related to the workflow of a construction process with the aid of a focus group formed with various construction industry representatives in New Zealand. The various problem-solving processes adopted by the industry practitioners at different functional levels are analysed and the findings summarised. Finally, this paper describes the development of one such mobile solution, called ClikiFax, which could address some of the issues and pressures prevailing in the context of the New Zealand construction industry.